2018
DOI: 10.1016/j.bbmt.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Early Increase in Complement Terminal Pathway Activation Marker sC5b-9 Is Predictive for the Development of Thrombotic Microangiopathy after Stem Cell Transplantation

Abstract: Hematopoietic stem cell transplantation (HSCT)-associated thrombotic microangiopathy (TA-TMA) is a multifactorial complication, and its prediction is largely unresolved. Our aim was to analyze changes of complement profile after HSCT to identify potential markers of TA-TMA development. Thirty-three consecutive pediatric patients (9.6 ± 4.4 years old) who underwent allogeneic HSCT due to malignant (n = 17) or nonmalignant (n = 16) indications were included in this study. Graft-versus-host disease (GVHD) was dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 34 publications
0
25
0
1
Order By: Relevance
“…Our previous investigations had demonstrated that plasma levels of C5b-9 and C3b were significantly increased in patients with TA-TMA [6]. An early rise in the C5b-9 level indicates poor prognosis of TA-TMA [25]. In these patients, complement factor autoantibodies and gene variations or mutations were found to be associated with TA-TMA [1,8], which is similar to the complement-mediated aHUS.…”
Section: Discussionmentioning
confidence: 83%
“…Our previous investigations had demonstrated that plasma levels of C5b-9 and C3b were significantly increased in patients with TA-TMA [6]. An early rise in the C5b-9 level indicates poor prognosis of TA-TMA [25]. In these patients, complement factor autoantibodies and gene variations or mutations were found to be associated with TA-TMA [1,8], which is similar to the complement-mediated aHUS.…”
Section: Discussionmentioning
confidence: 83%
“…In our previous study we utilized the advantages of our institutional protocol and conducted an explorative, consecutive, comprehensive analysis of complement biomarkers to search for TA-TMA associated, predictive biomarkers. Early increase of terminal pathway activation marker was identified as a sensitive marker of later development of TA-TMA (13). To decrease the risk of a false positive conclusion that may be related to the small size of our previous observational study, we found it of utmost importance to validate our initial observations in an independent cohort, before making any firm conclusions based on the initial data.…”
Section: Discussionmentioning
confidence: 91%
“…The sample and data collection as well as the methods used for the detection and analysis of complement parameters were described with full details in our previously published paper (13).…”
Section: Methodsmentioning
confidence: 99%
“…Care must be taken to rule-out conditions that can present with similar clinical and laboratory findings, such as veno-occlusive disease, infection, and GVHD. One recent reports suggests that a serial increase in serum levels of the terminal complement activation complex C5b-9 is a very sensitive predictor of subsequent TA-TMA [ 13 ]. While TA-TMA has been most closely linked to allogeneic SCT, it has also been described following autologous SCT as well [ 14 ], though this is far less common.…”
Section: Discussionmentioning
confidence: 99%